Enhancing student learning outcomes on cultural diversity through the cooperative learning model ‘Make a Match’ - Nuzulia Putri; Meriza Faradilla; Khairul Rizal (Pelita International Publishing, 2024)
This study aims to improve fifth-grade students' learning outcomes on cultural diversity using the cooperative learning model